2016
DOI: 10.1038/pr.2016.114
|View full text |Cite
|
Sign up to set email alerts
|

Human milk intake in preterm infants and neurodevelopment at 18 months corrected age

Abstract: Background:The effect of human milk intake on neurodevelopment in preterm infants is uncertain. Methods: We analyzed data from 611 participants in the DHA for Improvement of Neurodevelopmental Outcomes study, enrolled at ≤33 wk gestation from five Australian perinatal centers. The main exposures were (i) average daily human milk intake during the neonatal hospitalization and (ii) total duration of human milk intake before and after discharge. Outcomes were Bayley Scales of Infant Development, 2nd Edition Menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 29 publications
0
47
0
Order By: Relevance
“…[12] However, these infants were of higher GA and BW, had lower rates of most NICU morbidities and were born to a predominantly Caucasian, educated group of mothers who had a much higher rate of continuing HM feedings for their infants at NICU discharge (73% vs. 35%) as compared to our cohort. It is possible that post-discharge parenting practices and home environment had a greater influence for these infants than NICU HM dose, which may play a more significant role for higher risk populations such as ours.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…[12] However, these infants were of higher GA and BW, had lower rates of most NICU morbidities and were born to a predominantly Caucasian, educated group of mothers who had a much higher rate of continuing HM feedings for their infants at NICU discharge (73% vs. 35%) as compared to our cohort. It is possible that post-discharge parenting practices and home environment had a greater influence for these infants than NICU HM dose, which may play a more significant role for higher risk populations such as ours.…”
Section: Discussionmentioning
confidence: 78%
“…Although human milk (HM: from the infant’s own mother, excluding donor milk) feeding during the NICU hospitalization has been associated with improvements in ND outcome in premature infants, these earlier studies are limited by older cohorts and imprecise definitions of HM intake [49]. Studies that have found no association between HM and ND outcome have been limited by calculation of HM dose for only portions of the NICU stay [1012]. A number of these studies are comprised of homogenous cohorts and/or lower rates of HM use in minority populations, limiting generalizability to patients who might most benefit from higher HM intake [412].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 However, another cohort study in premature infants born £33 weeks gestation (N = 611) found no association between human milk intake and neurodevelopmental outcomes at 18 months. 16 The inconsistent results reported in these and other published studies evaluating the potential benefits of human milk in preterm infants may be due to differences in study populations, older nutrition practices that did not account for the greater needs of preterm infants, and the assessment of infant and toddler outcomes, which are poorly predictive of later cognitive abilities.…”
mentioning
confidence: 88%
“…First-week protein and energy intakes are associated with 18-month developmental outcomes,119 and meta-analysis has shown that increasing early enteral nutrition may reduce neurodevelopmental impairment 120. Preterm infants fed with predominantly breast milk had higher deep nuclear grey matter volume at term corrected age,121 improved developmental scores at 18 months122 as well as higher IQ and academic achievement at 7 years,121 although this has not been seen in all studies 123. Research is ongoing into optimal nutritional regimens; however, it is hypothesised the benefits of early nutrition and breast milk, including fortification, outweigh the risks 124…”
Section: Emerging Strategiesmentioning
confidence: 99%